1985
DOI: 10.1002/art.1780281009
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of sera from scleroderma patients on lymphocyte‐induced angiogenesis

Abstract: Sera from 22 patients with progressive systemic sclerosis were tested for the ability to modify the angiogeneic capability of normal human mononuclear cells. The sera from patients with acrosclerosis, including the abortive form (CREST syndrome: calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasias), markedly enhanced this capability compared with sera from both healthy donors and patients with severe acrosclerosis and diffuse scleroderma. The enhancing effect of sera from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
(5 reference statements)
0
11
0
1
Order By: Relevance
“…Several studies have demonstrated angiogenesis-related abnormalities, including decreased monocyte-mediated angiogenesis (35) and the presence of proangiogenic and antiangiogenic factors in SSc serum (36), including increased levels of circulating endostatin (37,38). At the same time, SSc serum was reported to enhance the angiogenic capability of circulating mononuclear cells (39). Finally, a recent gene expression study comparing transcriptomes of microvascular endothelial cells from normal control subjects and patients with SSc demonstrated overexpression of proangiogenic transcripts and both up-regulation of suppressor genes and downregulation of activator genes regulating cell migration in SSc endothelial cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated angiogenesis-related abnormalities, including decreased monocyte-mediated angiogenesis (35) and the presence of proangiogenic and antiangiogenic factors in SSc serum (36), including increased levels of circulating endostatin (37,38). At the same time, SSc serum was reported to enhance the angiogenic capability of circulating mononuclear cells (39). Finally, a recent gene expression study comparing transcriptomes of microvascular endothelial cells from normal control subjects and patients with SSc demonstrated overexpression of proangiogenic transcripts and both up-regulation of suppressor genes and downregulation of activator genes regulating cell migration in SSc endothelial cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Kaminski et al [19] isolated and purified lymphocytes from patients with SSc and showed that they exhibited less angiogenic activity than peripheral blood lymphocytes from healthy volunteers. These authors also showed that serum from SSc patients did not affect normal lymphocytemediated angiogenesis, but paradoxically, serum from patients with acrosclerosis markedly enhanced the angiogenic ability of healthy lymphocytes [20]. In addition, they demonstrated that semipurified SSc monocytes had enhanced angiogenic activity compared with healthy ones.…”
Section: Systemic Sclerosis Angiogenesis: Early Findingsmentioning
confidence: 93%
“…All patients were evaluated for internal organ involvement according to criteria given previously [9]. Antinuclear antibodies were measured by indirect immunofluorescence of HEp-2 cels [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown, for example, that serum factors from patients with acroscleroderma but not with diffuse scleroderma markedly enhance production of angiogenic lymphokines by normal human peripheral blood mononuclear cells [9].…”
Section: Introductionmentioning
confidence: 99%